Efusión pericárdica recurrente en un labrador con una masa sobre el atrio derecho : reporte de un caso clínico (2010)
ABSTRACT: This report describes a case of a nine-year-old Labrador that was presented to consultation with signs of anorexia, abdominal distension by ascitis, depression and exercise intolerance. A physical examination revealed low audible cardiac sounds, a weak femoral pulse, tachycardia, taquipnea and the presence of jugular pulse. Ancillary diagnostic methods determined that the patient was in cardiac tamponade by a pericardical effusion (PE). A pericardiocentesis was carried out and the fluid had a probable neoplastic origin. Five months later the patient presented again in cardiac tamponade and a pericardiocentesis was repeated. On this occasion a mass of 0,5 cm diameter was detected ecocardiographically on the external wall of the right atrium compatible with a primary hemangiosarcoma.